Motion and dural sac compression in the upper cervical spine during the application of a cervical collar in case of unstable craniocervical junction: a study in two new cadaveric trauma models - Liao, Shiyao; Schneider, Niko; Grützner, Paul Alfred; Weilbacher, Frank; Matschke, Stefan; Popp, Erik; Kreinest, Michael (PLOS ONE, 2018)
Background Unstable conditions of the craniocervical junction such as atlanto-occipital dislocation (AOD) or atlanto-axial instability (AAI) are severe injuries with a high risk of tetraplegia or death. Immobilization by a cervical collar to protect the patient from secondary damage is a standard procedure in trauma patients. If the application of a cervical collar to a patient with an unstable craniocervical condition may cause segmental motion and secondary injury to the spinal cord is unknown. The aim of the current study is (i) to analyze compression on the dural sac and (ii) to determine relative motion of the cervical spine during the procedure of applying a cervical collar in case of ligamentous unstable craniocervical junction. Methods and findings Ligamentous AOD as well as AOD combined with ligamentous AAI was simulated in two newly developed cadaveric trauma models. Compression of the dural sac and segmental angulation in the upper cervical spine were measured on video fluoroscopy after myelography during the application of a cervical collar. Furthermore, overall three-dimensional motion of the cervical spine was measured by a motion tracking system. In six cadavers each, the two new trauma models on AOD and AOD combined with AAI could be implemented. Mean dural sac compression was significantly increased to -1.1 mm (-1.3 to -0.7 mm) in case of AOD and -1.2 mm (-1.6 to -0.6 mm) in the combined model of AOD and AAI. Furthermore, there is a significant increased angulation at the C0/C1 level in the AOD model. Immense three-dimensional movement up to 22.9° of cervical spine flexion was documented during the procedure. Conclusion The current study pointed out that applying a cervical collar in general will cause immense three-dimensional movement. In case of unstable craniocervical junction, this leads to a dural sac compression and thus to possible damage to the spinal cord.
Gesehen am 14.02.2020